Carbon Nanotube Array Based Binary Gabor Zone Plate Lenses. Issue 1 (December 2017) - Deng, Sunan; Jwad, Tahseen; Li, Chi; Benton, David; Yetisen, Ali; Jiang, Kyle; Dai, Qing; Butt, Haider
Abstract Diffractive zone plates have a wide range of applications from focusing x-ray to extreme UV radiation. The Gabor zone plate, which suppresses the higher-order foci to a pair of conjugate foci, is an attractive alternative to the conventional Fresnel zone plate. In this work, we developed a novel type of Beynon Gabor zone plate based on perfectly absorbing carbon nanotube forest. Lensing performances of 0, 8 and 20 sector Gabor zone plates were experimentally analyzed. Numerical investigations of Beynon Gabor zone plate configurations were in agreement with the experimental results. A high-contrast focal spot having 487 times higher intensity than the average background was obtained.